2020
DOI: 10.1002/jmri.27087
|View full text |Cite
|
Sign up to set email alerts
|

Splenic T as a noninvasive biomarker for portal hypertension

Abstract: BackgroundThere is a need for noninvasive methods for the diagnosis and monitoring of portal hypertension (PH).PurposeTo 1) assess the correlation of liver and spleen T1 and T1ρ measurements with portal pressures in patients with chronic liver disease, and 2) to compare the diagnostic performance of the relaxation parameters with radiological assessment of PH.Study TypeProspective.SubjectsTwenty‐five patients (M/F 16/9, mean age 56 years, range 21–78 years) undergoing portal pressure (hepatic venous pressure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Renal allograft fibrosis, associated with the deposition of collagen in the cortical interstitial space, is considered an important factor for allograft prognosis. In another study, Hector et al (27) reported that spleen T1rho showed a significant correlation with portal pressure and clinically significant poral hypertension. It was suggested that the elevation in T1rho in the spleen with increased poral hypertension severity may reflect the deposition of collagen associate with fibrogenesis (27).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Renal allograft fibrosis, associated with the deposition of collagen in the cortical interstitial space, is considered an important factor for allograft prognosis. In another study, Hector et al (27) reported that spleen T1rho showed a significant correlation with portal pressure and clinically significant poral hypertension. It was suggested that the elevation in T1rho in the spleen with increased poral hypertension severity may reflect the deposition of collagen associate with fibrogenesis (27).…”
Section: Discussionmentioning
confidence: 92%
“…In another study, Hector et al (27) reported that spleen T1rho showed a significant correlation with portal pressure and clinically significant poral hypertension. It was suggested that the elevation in T1rho in the spleen with increased poral hypertension severity may reflect the deposition of collagen associate with fibrogenesis (27).…”
Section: Discussionmentioning
confidence: 92%
“…They reported that, in the spleens of the liver cirrhosis patients, there were diffuse 𝛼-smooth muscle actin expression of sinusoidal mesenchymal cells and deposition of collagen fibers on the perisinusoidal wall. Hectors et al [30] studied a prospective cohort of 25 patients with hepatic venous pressure gradient measurement. They found spleen T1rho significantly correlated with hepatic venous pres- Patients with liver fibrosis in Shenzhen data-1 have a trend of lower spleen DDVD values than those of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Among all relaxometry parameters, only spleen T1ρ significantly correlated with HVPG ( r = 0.613, p = 0.001) and demonstrated a significant ability to detect PH (0.817, p = 0.015) and CSPH (0.778, p = 0.024). Authors suggested that the better performance of spleen relaxometry measurements when compared to hepatic measurements could be related to possible cofounders preventing accurate hepatic assessment such as hepatic iron deposition and inflammation 116,119 . Furthermore, the large variability in pathophysiological characteristics between liver diseases may introduce inaccuracies when compared with the pathophysiological changes of PH in the spleen that may be less influenced by differences in disease etiology.…”
Section: Mri For the Assessment Of Portal Hypertensionmentioning
confidence: 99%